Fatty Acid Composition and Tocopherol Contents of some Sesame Seed Oils - Bertrand Matthäus; Mehmet Musa Özcan (Iranian Journal of Chemistry & Chemical Engineering, 2018)
In this study, the oil contents, fatty acid composition and tocopherol contents of sesame seed and oils belong to different countries were determined. The oil contents of materials changed between 49.22% (India) and 56.16% (Nigeria-Kanu). The major saturated fatty acids in sesame seed oils were palmitic (6.06-9.03%), stearic (5.29-6.42%) acids with small 20:0 (0.19-0.71%) acids. The main unsaturated fatty acids of sesame oil samples were linoleic (38.11-47.11%) and oleic (36.83-44.49%) acids. There was a significant difference in the amounts of the major fatty acids in the oil samples (P<0.05). The oils extracted from the Sesamum seeds were composed of 18.51-49.63 mg /100g γ-tocopherol, 0.134 mg/100g α-tocotrienol (India) and 0.415 mg/100g γ-tocotrienol (India). Total contents of tocopherol of samples ranged from 18.508 mg/100 g (Nigeria (Benue)) to 49.630 (Turkey (Mersin)).